Modified Reynolds Equation for Confined High Viscosity Film Lubrication and Lubrication Analysis of Micro-Tapered Pad Bearing - Kyosuke Ono (Tribology Online, 2023)
This study proposes a mathematical expression for the high-viscosity surface layer generated by the confinement of a lubricant film, which is evident in engine oil with a metallic detergent additive. The characteristics of a microtapered pad bearing lubricated by a confined high-viscosity film were clarified by solving a modified Reynolds equation for the confined high-viscosity lubricant film. The load capacity began to increase compared with that in the bulk viscosity case when the trailing gap decreased from twice the saturated high-viscosity layer thickness. The maximum value of the friction coefficient at the trailing gap near the layer thickness becomes remarkable compared with the case of the adsorbed high-viscosity layer model. Assuming that the increased effective viscosity caused by the confinement of the lubricant film is due to an adsorbed high-viscosity layer, the load capacity is significantly overestimated when the trailing gap is greater than the saturated high-viscosity layer thickness. Next, a mathematical expression of the synthetic viscosity of a lubricant with a polar additive having an adsorbed high-viscosity surface layer and a metallic detergent additive with a confined high-viscosity layer was proposed, and the characteristics of the microtapered pad bearings lubricated by the composite lubricant were investigated.